Art + Activism: Interventions from the academy : (Des.bordes: migration + solidarity) - Zambrano Murillo, María Giulianna; Garzón , Anamaría; Acosta , Sofia (Ánima, 2021)
In this essay, we present an account of Arte + Activismos"™ fourth edition. This is a research project developed since 2018 at the Universidad San Francisco de Quito. The event Des.bordes: Migration + Solidarity brought together six guests, to talk about creative processes created by migrant artists, and to share experiences related with activist and academic practices of documentation and forms of accompaniment to migrants"™ struggles.